Breakthroughs and Bottlenecks in Microbiome Research. Issue 4 (April 2021) - Liwinski, Timur; Leshem, Avner; Elinav, Eran
Abstract : Over the past 15 years, the research community has witnessed unprecedented progress in microbiome research. We review this increasing knowledge and first attempts of its clinical application, and also limitations and challenges faced by the research community, in mechanistically understanding host–microbiome interactions and integrating these insights into clinical practice.